A facile and general procedure to hyperporous carbons: carbonization of organic zinc salts. (September 2020) - Chen, Siru; Huang, Huiyong; Li, Yanqiang; Ma, Tingli
Abstract: A facile, one step procedure is proposed to prepare hyperporous carbons by using zinc organic salts as precursors. The volatile character of zinc at high temperature not only leads to high specific surface area, but also avoids the post-washing step after carbonization. The pore texture of the carbons can be easily turned by using different precursor and the factors that affect the porosity are examined in detail. It is found that a precursor with a high Zn/C ratio and chain-like structure tends to form high specific surface area carbons. The carbons show high potential when used for CO2 capture and electrode material of supercapacitor. Especially for Zn–C–C derived from zinc citrate, shows a high specific surface area of 2933 cm 3  g −1, a high CO2 uptake of 88 cm 3  g −1 at 298 K and a high capacitance of 260 F g −1 at a current density of 1 A g −1 . We believe that by choosing proper Zn organic salts precursors, carbonaceous materials with properties that surpass those reported here can be prepared and more application fields are waited to be extended by these carbons. Graphical abstract: A facile and general procedure was developed to synthesize porous carbons via using common Zn organic salts as precursors. The volatile character of zinc enables the high specific surface area of carbons. The obtained porous carbons can be used in various energy storage and conversion fields such as CO2 capture and supercapacitors. Image 1 Highlights: A series of porous carbons were synthesized by using organic zinc salts as precursors. A precursor with a high Zn/C ratio and chain-like structure lead to high surface area. The carbons show great potential in CO2 capture. The carbons also show high capacitance as electrode materials for EDLC. The Zn–C–Ce shows a specific surface area of 2933 cm 3  g −1 .